How to win an election - Wallace, Christine, 1960- (Sydney, NSW : NewSouth Publishing, 2020)
The 2019 Australian election produced a surprise result showing, not for the first time, that every election is there for the winning including the next one. Labor's surprise loss in 2019, like the Liberal and National parties' defeat in the so-called 'unloseable' 1993 election, showed how careful attention to basic political craft can yield big dividends and how inattention to it can turn apparently certain favourites into losers. With the vast challenges of climate change and social and economic equity in the post-pandemic world ahead of us, Australia cannot afford any more costly election accidents. How To Win An Election spells out the ten things a political leader and their party must excel at to maximise the chance of success, and against which they should be accountable between and during elections. Better performance in even a few of the areas canvassed in this book can change an election outcome, so full attention should be paid to each of them, all the time, every time, without fail, Wallace argues in real time when it counts. How To Win An Election is a crucial insurance policy against overconfident leaders imposing learner errors on their supporters over and over again, and for getting the best results from Australia's democratic system.
Title from title screen.
Includes bibliographical references.
Also available in print.
Mode of access : Available online.
Keywords: Australia. -- Parliament -- Elections -- 2019.; Elections -- Australia; Political campaigns -- Australia -- 21st century; Political campaigns -- Australia; Australia -- Politics and government -- 21st century; Electronic books